Systemic HMGB1 Neutralization Prevents Postoperative Neurocognitive Dysfunction in Aged Rats - Terrando, Niccolò; Yang, Ting; Wang, Xueqin; Fang, Jiakai; Cao, Mengya; Andersson, Ulf; Erlandsson, Harris Helena; Ouyang, Wen; Tong, Jianbin (Frontiers in Immunology, 2016)
Postoperative neurocognitive disorders are common complications in elderly patients following surgery or critical illness. High mobility group box 1 protein (HMGB1) is rapidly released after tissue trauma and critically involved in response to sterile injury. Herein we assessed the role of HMGB1 after liver surgery in aged rats and explored the therapeutic potential of a neutralizing anti-HMGB1 monoclonal antibody in a clinically relevant model of postoperative neurocognitive disorders. 19-22 months Sprague Dawley rats were randomly assigned as: (1) control with saline; (2) surgery, a partial hepatolobectomy under sevoflurane anesthesia and analgesia, + immunoglobulin G as control antibody; (3) surgery + anti-HMGB1. A separate cohort of animals was used to detect His-tagged HMGB1 in the brain. Systemic anti-HMGB1 antibody treatment exerted neuroprotective effects preventing postoperative memory deficits and anxiety in aged rats by preventing surgery-induced reduction of phosphorylated cyclic AMP response element-binding protein in the hippocampus. Although no evident changes in the intracellular distribution of HMGB1 in hippocampal cells were noted after surgery, HMGB1 levels were elevated on day 3 in rat plasma samples. Experiments with tagged HMGB1 further revealed a critical role of systemic HMGB1 to enable an access to the brain and causing microglial activation. Overall, these data demonstrate a pivotal role for systemic HMGB1 in mediating postoperative neuroinflammation. This may have direct implications for common postoperative complications like delirium and postoperative cognitive dysfunction.